PENGARUH HUMAN CAPITAL, STRUCTURAL CAPITAL, DAN RELATIONAL CAPITAL TERHADAP AKREDITASI UNIVERSITAS WIDYATAMA - Susanti, Neneng; Sujai, Raden Achmad Drajat Aji; Utami, Eristy Minda (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
The purpose of this research is to analyze the influence of human capital, structure capital, and relational capital on the accreditation of Widyatama University. This is an exploratory research applying associative research method. The data used is primary data. Data were analyzed using Structural Equation Modeling (SEM) with AMOS statistical software package. The results of this study show that human capital is the most dominant factor affecting accreditation, which is 15.35%, even though statistically it has no significant influence. Overall, intellectual capital factor has no effect on accreditation. Relational and structural capitals have negative effects on accreditation and statistically have insignificant influence. Keywords: Human Capital, Structure Capital, Relational Capital, Accreditation, and Widyatama University.